Factors affecting feeder pig auction price differentials - Ted C Schroeder; J M Jones; David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1988)
A survey of feeder pig sales was conducted at two Kansas feeder pig auctions during the spring and summer of 1988. Several factors were identified that helped explain a large portion of the short-run price differentials observed in feeder pig prices. Physical characteristics of the feeder pigs and changing market fundamentals during the data collection period accounted for 80 percent of the variability in feeder pig prices. The most significant physical characteristics affecting price included weight lot size health, structural soundness, lumps, ruptures and lot uniformity. There are clear incentives for producers to attempt to sell feeder pigs in healthy, structurally sound uniform-sized lots of 40 or more head.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Feeder pig pricing; Price differentials